Simultaneous Determination of Cr, As, Se, and Other Trace Metal Elements in Seawater by ICP-MS with Hybrid Simultaneous Preconcentration Combining Iron Hydroxide Coprecipitation and Solid Phase Extraction Using Chelating Resin - Akihide Itoh; Masato Ono; Kota Suzuki; Takumi Yasuda; Kazuhiko Nakano; Kimika Kaneshima; Kazuho Inaba (International Journal of Analytical Chemistry)
In the present study, ICP-MS with a new hybrid simultaneous preconcentration combining solid phase extraction using chelating resin and iron hydroxide coprecipitation in one batch at a single pH adjustment (pH 6.0) were developed for multielement determination of trace metal ions in seawater. In multielement determination, the present method makes it possible to determine Cr(III), As(V), Se (IV), and other 14 trace metal elements (Ti, V, Co, Ni, Cu, Zn, Zr, Ge, Cd, Sb, Sn, W, Pb, and U) in seawater. Moreover, for speciation analyses of Cr, As, and Se, the pH dependence on recovery for the different chemical forms of Cr, As, and Se was investigated. In speciation analyses, Cr, As, and Se were determined as the total of Cr (III) and a part of Cr (VI), total of As (III) and As (V), and Se(IV), respectively. Determination of total of Se and Cr(VI) remains as future task to improve. Nevertheless, the present method would have possibility to develop as the analytical method to determine comprehensively most metal elements in all standard and guideline values in quality standard in environmental water in Japan, that is, most toxic metal elements in environmental water.